(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The current research aims to test the role of psychological hardiness and its possibility in achieving organizational solidity and its impact on achieving the organization’s goals. The psychological hardiness variable includes three dimensions: (commitment, challenge, control) that are linked and their role in the dimensions of organizational solidity represented by (appropriateness, connections, and sacrifice) are known. This research relied on the data analytical approach, as it was applied to one of the educational institutions affiliated with Al-Furat Al-Awsat Technical University, which is the Technical Institute / Diwaniyah. The teaching staff at the institute was chosen as a sample for the study, and they numbered (120) teachers. After distributing the questionnaires to the sample and retrieving them, they were examined and invalid ones excluded. Therefore, the net sample suitable for analysis is (113) teachers. and the research hypotheses were tested using the simple correlation coefficient, multiple regression analysis, and a number of other statistical tools appropriate to achieve the objectives of the current research using the SPSS.v.24 program. The applied results of the research have proven the validity of the hypotheses that were proposed, on the basis of which the researchers concluded a number of results, the most prominent of which are the dimensions of psychological hardiness. These behaviors will cost them the sacrifice of many resources that could affect their lives inside and outside the organization in achieving organizational stability. Recommendations were formulated that were The most prominent of which is working to encourage working individuals to learn psychological toughness and strengthen it within the organization. The research also recommended making individuals feel the importance of the personal qualities and privileges that they possess when they are more capable of commitment, challenge and control, through publications and awareness seminars that explain the importance of these resources and the losses that individuals will incur in... The state of their sacrifice.